Surgical Management of Uterine Fibroids at Aminu Kano Teaching Hospital - Abiodun Omole-Ohonsi; Francis Belga (Hindawi Limited, 2012)
Objective. To determine the influence of age and parity on the surgical management of uterine fibroids, clinical presentation, presence of pelvic adhesions, cadre of surgeons, and postoperative complications at the Aminu Kano Teaching Hospital, Kano, Nigeria. Methods. A retrospective analysis of 105 cases of uterine fibroids that were managed between 1st January 2003 and 31st December 2007. Results. The period prevalence of uterine fibroids was 24.7% of all major gynecological operations. The mean age was 35.8 ± 7.6 and mean parity 4.7 ± 2.8. Abdominal hysterectomy accounted for 58.1% of the cases and myomectomy 41.9%. The odd of using abdominal hysterectomy was about twice that of myomectomy. Pelvic adhesions were found in 67.6% of the cases. Menorrhagia (86.7%) was the commonest symptom, while post operative anemia and pyrexia showed significant association with myomectomy. There was no maternal mortality. Conclusion. Surgical operations for uterine fibroids are safe and common kind of gynecological operations at the Aminu Kano Teaching Hospital. Uterine fibroid is associated more with high parity and dominance of abdominal hysterectomy over myomectomy, because early girl marriage is common in our community.